Regulatory non-coding RNAs: Emerging roles during plant cell reprogramming and in vitro regeneration - Cordeiro, Daniela; Canhoto, Jorge; Correia, Sandra (Frontiers in Plant Science, 2022)
Plant regeneration is a well-known capacity of plants occurring either in vivo or in vitro. This potential is the basis for plant micropropagation and genetic transformation as well as a useful system to analyse different aspects of plant development. Recent studies have proven that RNA species with no protein-coding capacity are key regulators of cellular function and essential for cell reprogramming. In this review, the current knowledge on the role of several ncRNAs in plant regeneration processes is summarized, with a focus on cell fate reprogramming. Moreover, the involvement/impact of microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and small-interfering RNAs (siRNAs) snRNAs in the regulatory networks of cell dedifferentiation, proliferation and differentiation is also analysed. A deeper understanding of plant ncRNAs in somatic cell reprogramming will allow a better modulation of in vitro regeneration processes such as organogenesis and somatic embryogenesis.